Pengaruh Corporate Social Responsibility, Profitabilitas, Leverage, dan Growth Terhadap Nilai Perusahaan - Aviyanti Winata; Titik Aryati (AKUA: Jurnal Akuntansi dan Keuangan, 2023)
Every company has a value that becomes an attraction for investors. Firm value is a benchmark for an investor to invest in the company. In addition to investors, the company's value can also be an attraction for the public to place their trust in the company. The more the company value increases, the more trust it will increase and will make it easier for the company to achieve its targets. The data used in this research are Corporate Social Responsibility, Profitability, Leverage, Growth and company value. The data collection technique was carried out using the documentation method. This method is carried out by recording or collecting data on companies included in the banking group during the 2018-2021 period, where this data is obtained from annual reports and those published by the Indonesian Stock Exchange (BEI) which can be accessed via each company's website. This sampling technique uses purposive sampling consisting of a sample of 46 banking companies listed on the IDX in 2018-2021. Data analysis using multiple linear regression. The results of research with 184 observations show that the Corporate Social Responsibility and Profitability variables have no effect on Company Value. Meanwhile, Leverage has a negative effect on Firm Value and Growth has a positive effect on Firm Value.